Cost analysis of hospitalized Clostridium difficile-associated diarrhea (CDAD) - Hübner, Claudia; Hübner, Nils-Olaf; Muhr, Michaela; Claus, Franziska; Leesch, Henning; Kramer, Axel; Flessa, Steffen (German Medical Science GMS Publishing House, 2015)
Aim: -associated diarrhea (CDAD) causes heavy financial burden on healthcare systems worldwide. As with all hospital-acquired infections, prolonged hospital stays are the main cost driver. Previous cost studies only include hospital billing data and compare the length of stay in contrast to non-infected patients. To date, a survey of actual cost has not yet been conducted.Method: A retrospective analysis of data for patients with nosocomial CDAD was carried out over a 1-year period at the University Hospital of Greifswald. Based on identification of CDAD related treatment processes, cost of hygienic measures, antibiotics and laboratory as well as revenue losses due to bed blockage and increased length of stay were calculated.Results: 19 patients were included in the analysis. On average, a CDAD patient causes additional costs of € 5,262.96. Revenue losses due to extended length of stay take the highest proportion with € 2,555.59 per case, followed by loss in revenue due to bed blockage during isolation with € 2,413.08 per case. Overall, these opportunity costs accounted for 94.41% of total costs. In contrast, costs for hygienic measures (€ 253.98), pharmaceuticals (€ 22.88) and laboratory (€ 17.44) are quite low.Conclusion: CDAD results in significant additional costs for the hospital. This survey of actual costs confirms previous study results.